2021
DOI: 10.1186/s12888-020-02991-5
|View full text |Cite
|
Sign up to set email alerts
|

Stigma of mental illness and cultural factors in Pacific Rim region: a systematic review

Abstract: Background Although cultural factors play a crucial role in experience of stigma, there is scant review on the impact and importance of culture on stigma of mental illness across Pacific Rim Region. This study aims to investigate: 1) the cultural factors related to stigmatizing beliefs about mental illness in Pacific Rim region, and 2) culture-specific measures and interventions on stigma of mental illness. Methods A systematic search of papers was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
69
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(72 citation statements)
references
References 57 publications
2
69
0
1
Order By: Relevance
“…Health policies should be developed for addressing the contact, especially positive contact, among CR, MHW, FM and persons with mental illness. Cultural-specific anti-stigma interventions should also account for the unique characteristics of different stakeholder groups (Ran et al, 2021). This study indicated that knowledge was significantly associated with the behaviours of MHW (e.g.…”
Section: Implications For Policy and Servicesmentioning
confidence: 99%
See 1 more Smart Citation
“…Health policies should be developed for addressing the contact, especially positive contact, among CR, MHW, FM and persons with mental illness. Cultural-specific anti-stigma interventions should also account for the unique characteristics of different stakeholder groups (Ran et al, 2021). This study indicated that knowledge was significantly associated with the behaviours of MHW (e.g.…”
Section: Implications For Policy and Servicesmentioning
confidence: 99%
“…Stigma of mental illness is a global public health issue (Henderson & Thornicroft, 2009; Ran et al, 2021; World Health Organization [WHO], 2013). According to social cognitive model of stigma (Corrigan et al, 2003, 2014), which built on attribution theory (Weiner, 1988) and theory of dangerousness (Angermeyer et al, 2004), stigma of mental illness is conceptualized in terms of stereotypes (negative beliefs about persons with mental illness (PMI), e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Based on literature and current data from this study, the following discussion addresses two signi cant public stigma predictors and three non-signi cant results. In a systematic review of 41 studies in the Paci c Rim region, Ran et al [43] found that cultural factors led to the stigma of mental illness. Speci cally, Chinese people who are collectivist-oriented believe that mental illness is equivalent to secrecy, internalizing it with self-stigma but accepting "one's role as handed down by destiny" [16 p. 38].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, prior evidence from non-parent population suggests that women may be more likely to perceive and internalise stigma compared to men (Jenkins & Carpenter-Song, 2008). Additionally, only few literatures have focused on the impact of culture on mental illness among patients' with schizophrenia (Ran et al 2021) with none among female parents with schizophrenia in the context of parenting. The available ones on the relationship of culture and stigma either evaluated on the cross-cultural differences in the levels of stigma (Abdullahi & Brown, 2011) or on the ethno-cultural beliefs, values and norms that shape stigma of mental illness (Ran et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, only few literatures have focused on the impact of culture on mental illness among patients' with schizophrenia (Ran et al 2021) with none among female parents with schizophrenia in the context of parenting. The available ones on the relationship of culture and stigma either evaluated on the cross-cultural differences in the levels of stigma (Abdullahi & Brown, 2011) or on the ethno-cultural beliefs, values and norms that shape stigma of mental illness (Ran et al 2021). As Cultural beliefs and practices are also integral to understanding stigma of mental illness among special group of individual, cultural practices and beliefs that further compounds stigma among female parents (mothers) with schizophrenia have not been explored in Nigeria.…”
Section: Introductionmentioning
confidence: 99%